Aicardi Syndrome: A Case Report of a 7 Months Old Girl with Infantile Spasm, Ocular Abnormalities and Severe Psychomotor Retardation (Bangladesh Journal of Neuroscience, 2026)
Aicardi syndrome a rare form of neurodegenerative encephalopathy affecting mostly woman as it follow X-linked recessive inheritance. It has a classical triad for diagnosis which is composed of agenesis of corpus callosum, infantile spasm and chorioretinal lacunae. Patients may have also the additional features of microcephaly, severe psychomotor retardation and spasticity. Male are embryonically lethal in early gestation so female are the only sufferer. Here we reporting a 7 months old girl who had history of recurrent spasm, global developmental delay and bilateral clouding of cornea, her MRI of brain have shown features of hypoplastic corpus callosum, prominent megacistern, cortical atrophy, eye findings have shown bilateral corneal haziness multifocal discharge on EEG findings. We have counseled the parents and treated the patients by anticonvulsants, anti spastic medication. We have also initiated rehabilitation by providing developmental therapy, and opthalmological consultation.